ПЕРЕХОДНЫЕ ПРОЦЕССЫ В RLC-ЦЕПИ С ГЕТЕРОГЕННОЙ ПЛАЗМОЭРОЗИОННОЙ НАГРУЗКОЙ - Шидловская , Н.А.; Захарченко , С.Н. (Інститут електродинаміки НАН України, Київ, 2014)
The nonlinear-parametrical equivalent circuit of heterogeneous plasma-erosive load for a wide frequency band is offered. The analytical models describing transients in a RLC-circuit with such loading, as generally, and in cases of nonlinear and parametrical dependence of resistance of loading are developed. Dependences on a proceeding current of equivalent electric resistance of a layer of metal granules, and also the waters described by hyperbolic functions of the first order are considered. Parametrical dependence of resistance of a layer of the granules, described by function on the basis of the sum two exponents is considered. Solutions of the differential equation describing transients in the given circuit for above mentioned special cases for nonlinear and parametrical dependences of resistance of a layer of granules and water in band of low, average and high frequencies of discharge pulses are received. References 10, figure 1.